Psychological capital and entrepreneurial outcomes: The moderating role of social competences of owners of micro-enterprises in East Africa - Martin Mabunda Baluku; Julius Fred Kikooma; Edward Bantu; Kathleen Otto (Journal of Global Entrepreneurship Research, 2018)
Business success arises out of the total investments in the venture. This is not limited to tangible inputs such as financial capital, but on intangible resources as well. Entrepreneurship is a highly stressing occupation involving undertaking risks and often demanding workloads; hence requiring mental inputs (psychological capital). Moreover, the entrepreneurial job also involves doing business with other people of different statuses including investors, partners, customers, and employees; hence requiring the entrepreneur to exhibit a great deal of social competence to relate with others. Using two independent studies, we assess the contribution of psychological capital and social competence, as well as their interaction to entrepreneurial outcomes including performance (Study 1), and entrepreneurs' wellbeing, satisfaction, and commitment to their entrepreneurial career role (Study 2). Study 1 uses a sample of 102 owner-managers or managers of small companies in Uganda. In this study, entrepreneurs' social competence is measured as the relationship between entrepreneurs and their employees. Study 2 uses a sample of 228 young self-employed individuals in Uganda and Kenya; and operationalizes social competence via social intelligence. The results were consistent with our assumptions, highlighting the relevance of both psychological capital and social competence to entrepreneurial outcomes. Yet their interaction also has substantial impact on all outcomes examined in these studies.
Keywords: 650; Commitment to entrepreneurship; Entrepreneurial outcomes; Performance; Psychological capital; Psychological resources; Satisfaction; Social competence; Well-being